Organisational resilience of entrepreneurial enterprises during crises: A case study of saturnbird coffee - You, Yue; Fatmawati, Latada (Global Academic Excellence (M) Sdn. Bhd., 2025)
This study investigates the organisational resilience of entrepreneurial enterprises in the face of crises, using the emerging Chinese coffee brand Saturnbird as a case example. Drawing on the three-stage model of organisational resilience (anticipation, coping, adaptation), the analysis reveals that Saturnbird demonstrated a high degree of strategic agility, digital capability, and user co-creation culture during the COVID-19 pandemic, effectively responding to market uncertainties. The findings confirm that organisational resilience is a dynamic capability that can be developed and transformed into competitive advantage, particularly for entrepreneurial enterprises. This research enriches the application of resilience theory in entrepreneurial contexts and provides practical insights for small and medium-sized enterprises operating in resource-constrained environments.